Post‐Synthetic Modification of Porous Organic Cages for Enhanced Iodine Adsorption Performance - Qianqian Mao; Siyuan Yang; Jinjin Zhang; Yuanhan Liu; Ming Liu (Advanced Science)
Abstract The capture of radioactive iodine species from nuclear waste is crucial for environmental protection and human health. Porous organic cages (POCs), an emerging porous material, have showed potential in iodine adsorption due to the advantages of tunable pores and processibility. However, integrating multiple desirable characteristics into a single POC through bottom‐up assembly of pre‐designed building blocks remains challenging. Post‐synthetic modification (PSM) offers an alternative approach, enabling the introduction of various functions into a single POC. Herein, a viable and highly efficient three‐step PSM strategy to modify a representative POC (CC3), is presented. The modified POC, OFT‐RCC36+6Br−, features a charged confined space, electron‐rich heteroatom, and halide ions, exhibiting significantly enhanced iodine vapor uptake compared to the parental cage. The universality of the PSM strategy has been verified by successfully modifying two other POCs. The iodine adsorption behaviors of three modified cage adsorbents in organic solvent and aqueous solution have also been investigated, all of which exhibited improved performance, especially in comparison to ionic cages modified through direct protonation. This work provides an effective PSM strategy for POCs to facilitate iodine adsorption. More importantly, the introduction of a new PSM strategy enriches the functional diversity of POCs, potentially broadening their future applications.